Aetio Pathogenesis Of Optic Atrophy: Case Study - ,Dr.P.Ravi Kumar, Dr.V.Murali Krishna, Dr.APR Naidu, (International Journal of Scientific Research and Management (IJSRM), 2015)
The term optic atrophy describes a group of clinical conditions which have an abnormal pallor of the disc as a common physical sign. Optic atrophy is not a disease; it is the end result of any pathologic process that damages the retinal ganglion cells and axons of the retinogeniculate pathway. In other words, optic atrophy is defined as a condition characterized by the loss of conducting function of the optic nerve.